A Call to Action: A Blueprint for Academic Health Sciences in the Era of Mass Incarceration. - Ferguson, Warren J; Cloud, David; Spaulding, Anne C; Shelton, Deborah; Trestman, Robert L; Altice, Frederick L; Champion-Lippmann, Carisa; Thomas, David; Taxman, Faye S (Journal of health care for the poor and underserved, 2016)
Over 100 million Americans have criminal records, and the U.S. incarcerates seven times more citizens than most developed countries. The burden of incarceration disproportionately affects people of color and ethnic minorities, and those living in poverty. While 95% of incarcerated people return to society, recidivism rates are high with nearly 75% arrested again within five years of release. Criminal records impede access to employment and other social services such as shelter and health care. Justice-involved people have higher rates of substance, mental health, and some chronic medical disorders than the general population; furthermore, the incarcerated population is rapidly aging. Only a minority of academic health science centers are engaged in health services research, workforce training, or correctional health care. This commentary provides rationale and a blueprint for engagement of academic health science institutions to harness their capabilities to tackle one of the country's most vexing public health crises.